‘Art Barricades’ and ‘Poetic Legitimation’ for squatted spaces: Metropoliz, Rome and Cavallerizza Reale, Turin - Bragaglia, Francesca; Krähmer, Karl (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2018)
Can art legitimise squatting? We examine this question through two case studies: Metropoliz in Rome – an old industrial building occupied by a multiethnic community – and Cavallerizza Reale in Turin – a historical complex occupied by active citizens. Both experiences use art, and the capital of attention and market value associated to it, as a tool to protect themselves from eviction. But art has become in the last decades both an economic good in which to invest capital and an instrument of neoliberal and post-fordist urban policies, linked to concepts such as Florida’s “creative class”. Now, members of precisely this class, who supposedly benefit from this model, engage, alongside others, in urban resistance. If using art in this form is an intelligent way to exploit it’s market value to protect projects aiming at the right to the city or rather means to succumb, at last, to the dominant model, is debated also among the activists themselves. Key words: Squatting, Art, Right to the City, Creative Class, Self-Organization L'arte può legittimare le occupazioni illegali? L’articolo affronta la questione attraverso due casi studio: Metropoliz a Roma - ex-edificio industriale occupato da una comunità multietnica - e la Cavallerizza Reale a Torino, complesso storico occupato da cittadini attivi. Entrambe le esperienze utilizzano l'arte e l’attenzione pubblica e il valore di mercato associati ad essa come strumento per proteggersi dal rischio di sgombero. L'arte però è diventata negli ultimi decenni anche un bene economico in cui investire e uno strumento di politiche urbane neoliberiste e post-fordiste, legate a concetti come quello di "creative class" di Florida. Ora proprio alcuni membri della classe creativa, che avrebbero dovuto beneficiare di questo modello, si impegnano in esperienze di attivismo urbano. Usare l'arte in questa forma può essere un modo per sfruttare il suo valore di mercato per tutelare progetti mirati al diritto alla città o significa piuttosto soccombere al modello dominante? Parole chiave: Squatting, Arte, Diritto alla città, Creative Class, auto-organizzazione